Precision of Ci-navigated extension and flexion gap balancing in total knee arthroplasty and analysis of potential predictive variables - Fickert, Stefan; Jawhar, Ahmed; Scharf, Hanns-Peter (Archives of orthopaedic and trauma surgery, 2012)
IntroductionThe aim of this study was to evaluate the accuracy of final limb alignment and flexion-extension and medial-lateral gap balancing in computer navigated total knee arthroplasty and to analyze various possible predictive variables that may affect the gaps in computer navigated knee arthroplasty.Materials and methodsThe DePuy Ci system, a nonimage-based passive optical computer navigation system, was used in 225 patients with knee osteoarthritis to assist for the total knee arthroplasty. From the raw data the Ci-verified pre- and postoperative leg axis in extension, angle of tibia and femur resection, the flexion and extension angle, the medial and lateral extension and flexion gaps were extracted; and differences in gaps were calculated and subjected to statistical analysis. Leg alignment and implant position were determined only by the navigation system. Preoperative variables were evaluated for their impact on the final flexion/extension and medial/lateral gaps achieved.ResultsThough the preoperative femoro-tibial coronal alignment had a large variance, postoperatively 98.22% of the knee was found to be between −3° and +3° in the coronal limb alignment axis. The Ci-verified femoral and tibial cuts in the coronal plane showed a good accuracy. The sagittal alignment of the femoral cut ranged from 8.20° flexion to 3.20° of extension. Rectangular extension and flexion gaps were achieved with ≤3 mm of difference in gaps on medial and lateral sides in 98 and 93% of knees, respectively. Difference between extension and flexion gaps on the medial side was ≤3 mm in 83% and on the lateral side in 84% of the knees. Of all the possible predictive variables analyzed, Pearson correlation and multiple regression analysis showed significant correlation only between the medial-lateral gap difference in extension and the Ci-verified femoral cut, tibial cut and limb axis, all in the coronal plane.ConclusionComputer-assisted navigated total knee replacement allows for accurate gap balancing that is not dependent on the various pre- and intraoperative factors mentioned, including age, sex, Range of motion preoperative deformity and grade of osteoarthritis. The Ci-calculated and verified tibial, and femoral cuts are the only possible factors affecting the extension gap.